Adaptação transcultural do "EULAR Sjögren's syndrome disease activity index (ESSDAI)" para a língua portuguesa brasileira - Serrano, Érica Vieira (2012)
Introduction: The EULAR Sjögren s Syndrome Disease Activity Index (ESSDAI) is a composite index to assess systemic activity of primary Sjögren s Syndrome (SSP) created in 2009 and it does not have any cultural adaptation to Portuguese language. Objective: To perform the cultural adaptation of ESSDAI for Brazilian Portuguese. Methods: Cross-sectional observational study with patients with SSP according to the European American Consensus 2002. In the adaptation process, there were six steps: conceptual equivalence, item, semantic, operational, measurement and functional. Semantic equivalence included translation, back translation, evaluation of semantics between the original and back translations, discussion with experts for final adjustments and pre-test of consensual version in twenty patients. In measurement equivalence, the psychometric properties of internal consistency, interobserver reproducibility and construct validity were assessed in 62 subjects. For the construct validity, the ESSDAI was compared with the Physician s Global Assessment (PhGA), the Sjögren s Syndrome Disease Activity Index (SSDAI), the Sjögren s Systemic Clinical Activity Index (SCAI), between groups "active" and "inactive" defined by expert and according to intention to treat, the groups "increase therapy" and "no increase in therapy." Statistical tests used were Cronbach s α for internal consistency, the intraclass correlation coefficient and Bland Altman analysis for interobserver reproducibility, and the Spearman coefficient and Mann-Whitney test for validity (p <0.05 and CI: 95%). Results: There were no differences in the versions in both languages, giving the Brazilian consensual version. The sample consisted of women, aged 49.4 ± 11.6 years. The onset of symptoms was 7.2 ± 5.4 years and the time of diagnosis was 3.0 ± 3.3 years. The average score of the total score ESSDAI was 4.95 ± 6.73. Frequency domain was: 40.3% biological, 40.3% hematological, 27.4% articular, 14.5% respiratory, 11.3% peripheral nervous system, 9.7% constitutional, 8.1% renal, 8.1% glandular, 4.8% skin and 1.6% lymphadenopathy. Domains of the central nervous system and the muscles scored zero in all patients. Internal consistency was low and interobserver reproducibility of ESSDAI had a high intraclass correlation coefficient of 0.89 and good agreement by Bland Altman. In construct validity, the correlation with PhGA was 0.83 (p <0.000, Spearman coefficient), with SSDAI was 0.658 (p <0.000), and with SCAI was 0.411 (p = 0.001). Mann-Whitney test showed that the group "active" and the group "needed increased therapy" obtained the higher values in ESSDAI (p = 0.000). Conclusion: The Portuguese version of ESSDAI proved to be an adaptable instrument, reproducible and valid for Portuguese and can be used in the Brazilian context.